Losses Due to Bird. Damage in Different Jujube Cultivars - Singh, M P; Vashishtha, B B (Annals of Arid Zone, 2016)
Studies to assess the extent of bird damage to different Zizyphus mauritiana cultivars were carried out for three consecutive fruiting seasons. A mean fruit loss of 13-20% was recorded in different cultivars in guarded orchards. The birds did not exhibit preference for any particular cultivar in field. The maximum injury was inflicted to the semi-ripe fruits, followed by ripe and unripe fruits.